RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJA PETERNAKAN SAPI DI PT X CABANG KOTA KEDIRI - Cokorde Dhio Pranamyaditia (Universitas Airlangga, 2016)
The ranch has many risks, risks that could cause transmission of disease, injury, broken bones, entry of the parasite, up to the dead. In the world of farming in Indonesia is still not pay attention to the job safety for workers. The purpose of this study was to know risk on farm workers PT X branch Kediri. This research was an observational study with cross sectional and descriptive analysis. The data used are primary data from interviews and observations, secondary data derived from the company. The results showed that the hazard identification based on 8 jobs on farms PT X branch in Kediri found 49 hazards. Based on the risk assessment conducted on the 49 hazards can be classified into 36 low risk, 10 medium risk and 3 high risk. Risk control is performed administrative control and use of personal protective equipment. The conclusion of this study 3 high risk was contamination, kicked on cleaning job and kicked on maintenance job. Risk control by PT X lacking in some aspects (attention to the quality of personal protective equipment, the completeness of personal protective equipment workers, and control of sewage cow). Suggestions for improving the quality of livestock is take a concerted gloves and uniforms more appropriate, training on how to handle cattle, how to set up a safe working position, modification of the cage, as well as companies providing the means for individual hygiene.Keywords: Heath and Safety Risk, cattle farm workers, beef cattle